2019
DOI: 10.1002/ese3.449
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent wind turbine blade icing detection using supervisory control and data acquisition data and ensemble deep learning

Abstract: Ice accretion on wind turbine blades is one of the major faults affecting the operational safety and power generation efficiency of wind turbines. Current icing detection methods are based on either meteorological observing system or extra condition monitoring system. Compared with current methods, icing detection using the intrinsic supervisory control and data acquisition (SCADA) data of wind turbines has plenty of potential advantages, such as low cost, high stability, and early icing detection ability. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 34 publications
(37 reference statements)
0
27
0
Order By: Relevance
“…Successively, they also utilized denoising autoencoders, enriched with temporal information to assess turbine conditions in a laboratory and online scenario [17]. Finally, autoencoders have been successfully used for ice-detection on turbines' blades by Liu et al [18].…”
Section: Introductionmentioning
confidence: 99%
“…Successively, they also utilized denoising autoencoders, enriched with temporal information to assess turbine conditions in a laboratory and online scenario [17]. Finally, autoencoders have been successfully used for ice-detection on turbines' blades by Liu et al [18].…”
Section: Introductionmentioning
confidence: 99%
“…A meta-learner trained on a subset of base predictors has been used to improve wind power production in [ 38 , 39 ]. Liu et al proposed a solution to detect wind turbine blades icing combining features extracted by Deep-Autoencoders into an ensemble model where decision is taken by majority vote [ 40 ]. Ensembles can be used to merge information from different data sources, as Turnbull et al demonstrated using a OCSVM to combine NBMs of a temperature SCADA and vibration data for gearbox and generator bearings of wind turbines [ 41 ].…”
Section: Previous Workmentioning
confidence: 99%
“…The limitation of shallow machine learning methods is that the process for obtaining such features is usually time-consuming and can be very expensive. Deep learning-based methods attempt to model high-level representations of sensor data and identify icing conditions via a hierarchical structure [10], [16], [21], which is more competitive in terms of performance than shallow machine learning methods are.…”
Section: Introductionmentioning
confidence: 99%
“…However, to the best of our knowledge, their use in detecting icing on wind turbine blades has not yet been extensively studied [10], [12], [21]. There are even fewer studies of deep learning-based methods for icing detection [10].…”
Section: Introductionmentioning
confidence: 99%